CEOs Remuneration in Corporate Governance Codes in EU Member Countries - Urbanek, Piotr (Comparative Economic Research. Central and Eastern Europe, 2010)
Over the past two decades corporate governance has become one of the key issues in business and academic debates. The appropriate standards of corporate governance constitute important components of successful market economies. At the same time it is widely emphasized that contemporary mechanisms by which enterprises are directed and controlled are seriously defective. There is a need for profound reforms in corporate governance mechanisms. The growing interest in corporate governance codes among OECD countries is a very important component of these reforms. The purpose of the paper is to compare regulations in corporate governance codes in 27 EU countries concerning remuneration of top executives. It enables identifying two main mechanisms which are implemented in CG codes – market mechanism based on high level of remuneration transparency and hierarchical mechanism based on setting rules according to which corporate boards establish a formal procedure for fixing the remuneration packages of executives. The paper presents the discussion on determinants of these two mechanisms.